The brave new wired world. - Burton, Daniel F. (Foreign Policy)
The emergence of the networked economy is a catalyst behind the foreign policy debate. In such an economy, the combination of computing and communications creates an electronic marketplace that is completely dependent on powerful information networks. As a pioneer of this economy, the United States will play a defining role in its evolution and is therefore poised to create the domestic policies required to make the networked economy function and to alter the face of foreign policy. In order to comprehend the forces driving this new world, the United States must understand the evolution of computer networks. In order to take advantage of such a world, it is necessary to understand the trends that drive the networked economy, and a new set of benchmarks that indicate the extent of infrastructure and usage must be used in order to determine America's standing.